Assessment of the vulnerability of coastal mangrove ecosystems in Mozambique - Charrua, Alberto Bento (2020)
Mangrove forests are among the most productive ecosystems on Earth. However, there is still insufficient information available for strategic prediction of conservation and management intervention, particularly in the case of Mozambique. This country has the longest coastline and mangrove forests of Eastern Africa, but is prone to global climate hazards. Using recent field data and environmental parameters subjected to the Variance Inflation Factor (VIF) collinearity test (bioclimatic variables, slop, salinity, land cover, and elevation), we ran MaxEnt to model the distribution of mangrove forests based on occurrence data of the most emblematic and representative mangrove species in Mozambique (Avicennia marina and Rhizophora mucronata). Moreover, in order to understand which areas should be prioritized for management interventions on mangroves and costal dunes, an Exposure Index (EI) to climate hazards and erosion was compared with the potential distribution of these species. Our results showed that average wind speed of summer season, land surface elevation, Mean Diurnal Range, and saltwater exposure (salinity) were determinant on the distribution models of both species. The central coastal region of Mozambique (so-called swamp coast) presents the largest potentially suitable areas for mangroves species occurrence, having the highest levels of exposure. We also found that A. marina presents a higher EI than R. mucronata. The scarcity of studies concerning the central region of Mozambique; which was recently devastated by cyclone Idai (category four, 2019), which hit Mozambique and the neighbouring countries, reinforce the urgency for management intervention. The findings of this study should be used by managers and decision makers to promote best practices to safeguard lives and people's livelihoods and assets threatened by coastal climate hazards and anthropogenic impacts.